Analisis Perilaku Personal Hygiene dan Tingkat Stres dengan Kejadian Keputihan Patologis pada Remaja Putri di SMK N 6 Padang - Ayu Rahma Sari; Bobby Indra Utama; Netti Suharti; Vaulinne Basyir; Amel Yanis; Linosefa Linosefa (Jurnal Kesehatan Komunitas, 2026)
According to the Indonesian Adolescent Reproductive Health Survey (SKKRI), the incidence of vaginal discharge among Indonesian women has continued to increase from 2019 to 2021. Vaginal discharge can be caused by poor personal hygiene and stress which can affect hormonal function in women. This study aims to analyze the relationship between personal hygiene behaviors and stress levels to the incidence of vaginal discharge. This study used a cross-sectional approach. The study was conducted at SMK N 6 Padang from March to September 2025. A sample of this study is 278 adolescent girls was selected using a proportional stratified sampling technique. Data processing was analyzed using chi-square test. The results showed that the majority of respondents had good personal hygiene practices (50,0%), moderate stress levels (83,5%) and experienced pathological vaginal discharge (24,8%). Statistical test showed a relationship between personal hygiene behavior with incidence of vaginal discharge in adolescent girls (p=0,001) and stress levels (p=0,005). The conclusion of this study is there’s a relationship between personal hygiene behavior and stress levels with incidence of vaginal discharge in adolescent girls at SMK N 6 Padang. It is recommended that adolescent girls maintain good personal hygiene practices, maintain personal hygiene and manage stress effectively.